Pasak estetik dari bahan fiber reinforced composite Esthetic post made of fiber reinforced composite materials - Emy Ardana; Aries Chandra Trilaksana (Journal of Dentomaxillofacial Science, 2013)
The prosthetic treatment of seriously damaged teeth after treated with endodontic often require an endodontic post asan additional retention element for core build-up prior to crown restoration. In addition to metal-based posts andzirconia-based ceramic posts, fiber reinforced composite (FRC) post system has become to be widely used in therestoration of endodontically treated teeth. A FRC post offers a number of advantages over a metal post due to itsmodulus of elasticity being closer to that of dentin and superior esthetic quality. Teeth restored with FRC posts showbetter resistance to fracture propagation than teeth restored with prefabricated or cast metal posts. Endodonticallytreated teeth reinforced with a prefabricated fiber post have shown lower incidences of root fracture.